circHIPK3 Exacerbates Folic Acid-Induced Renal Tubulointerstitial Fibrosis by Sponging miR-30a - Wu, Yan; Luan, Junjun; Jiao, Congcong; Zhang, Shiwen; Ma, Cong; Zhang, Yixiao; Fu, Jingqi; Lai, En Yin; Kopp, Jeffrey B.; Pi, Jingbo; Zhou, Hua (Frontiers in Physiology, 2022)
Renal tubulointerstitial fibrosis is common pathological feature of progressive chronic kidney disease and current treatment has limited efficacy. The circular RNA circHIPK3 is reported to participate in the pathogenesis of various human diseases. However, the role of cicHIPK3 in renal fibrosis has not been examined. In this study, we aimed to determine whether and how circHIPK3 might participate in the pathogenesis of renal fibrosis. Mice received a peritoneal injection of folic acid (250 mg/kg). Thirty days later, renal fibrosis was present on periodic acid-Schiff and Masson staining, and mRNA and protein of profibrotic genes encoding fibronectin and collagen 1 were increased. Renal circHIPK3 was up-regulated, while miR-30a was down-regulated, assessed by qPCR and fluorescence in situ hybridization (FISH). Expression of transforming growth factor- β 1 (TGF-β1) was increased by analysis of qPCR, immunoblotting and immunofluorescence. Renal circHIPK3 negatively correlated with miR-30a, and kidney miR-30a negatively correlated with TGF-β1. Target Scan and miRanda algorithms predicted three perfect binding sites between circHIPK3 and miR-30a. We found that circHIPK3, miR-30a, and TGF-β1 co-localized in cytoplasm of human tubular epithelial cells (HK-2 cells) on FISH and immunofluorescence staining. We transfected circHIPK3 and a scrambled RNA into HK-2 cells; miR-30a was down-regulated and profibrotic genes including TGF-β1, fibronectin, and collagen 1 were up-regulated, assessed by qPCR, immunoblotting and immunofluorescence staining. Third, the upregulation of circHIPK3, downregulation of miR-30a, and overproduction of profibrotic fibronectin and collagen l were also seen in HK-2 cells exposed to TGF-β1. Lastly, renal biopsies from patients with chronic tubulointerstitial nephritis manifested similar expression patterns of circHIPK3, miR-30a, and profibrotic proteins, including TGF-β1, fibronectin and collagen l as seen in the experimental model. A feed-forward cycle was seen among circHIPK3, miR-30a, and TGF-β1. Our results suggest that circHIPK3 may contribute to progressive renal fibrosis by sponging miR-30a. CircHIPK3 may be a novel therapeutic target for slowing the chronic kidney disease progression.